Return Volatility of Green Sukuk in The Islamic Capital Market: A Comparative Study Between Indonesia and Malaysia - Hakim, Lukman; Susilowati, Dewi (Islamic Economic Scholar Association and Faculty of Economics and Business Universitas Jenderal Soedirman, 2025)
Sustainable development is increasingly vital in climate-vulnerable countries such as Indonesia and Malaysia, where green sukuk Sharia-compliant financial instruments play a key role in funding environmentally sustainable projects. This study employs a quantitative method using multiple linear regression to analyze factors influencing green sukuk return volatility in both countries. Secondary data on price movements and returns were obtained from capital market reports, followed by classical assumption testing to ensure data reliability and validity. The findings reveal that taxes, exchange rates, money supply, and interest rates significantly affect return volatility, with exchange rates and money supply exerting stronger effects in Malaysia, while tax-related volatility is more pronounced in Indonesia due to fiscal instability. These results suggest that Indonesia should focus on stabilizing fiscal policies and raising public awareness, whereas Malaysia should strengthen its support for green investment initiatives. Overall, the study contributes to enhancing Islamic finance resilience and promoting sustainable development.